2021
DOI: 10.3390/biom11060814
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Metformin in Diabetic and Non-Diabetic Rats with Experimentally-Induced Chronic Kidney Disease

Abstract: This work aimed to investigate whether treatment with the antidiabetic drug metformin would affect adenine-induced chronic kidney disease (CKD) in non-diabetic rats and rats with streptozotocin (STZ)-induced diabetes. Rats were randomly divided into eight groups, and given either normal feed, or feed mixed with adenine (0.25% w/w, for five weeks) to induce CKD. Some of these groups were also simultaneously treated orally with metformin (200 mg/kg/day). Rats given adenine showed the typical signs of CKD that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 58 publications
2
16
0
1
Order By: Relevance
“…For example, AdipoRon, a small-molecule agonist of adiponectin receptor is used at 50 mg/kg BW [ 29 ], curcumin at 100 mg/kg BW [ 30 ], soy β-Conglycin at 10% of diet ( w / w ) [ 31 ] and the di-peptide (Trp-His) at dosages ranging between 10–100 mg/kg BW [ 32 , 33 ]. Moreover, metformin is used at 200 mg/kg BW in rodent models of diabetes [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, AdipoRon, a small-molecule agonist of adiponectin receptor is used at 50 mg/kg BW [ 29 ], curcumin at 100 mg/kg BW [ 30 ], soy β-Conglycin at 10% of diet ( w / w ) [ 31 ] and the di-peptide (Trp-His) at dosages ranging between 10–100 mg/kg BW [ 32 , 33 ]. Moreover, metformin is used at 200 mg/kg BW in rodent models of diabetes [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overproduction of ROS and the inadequate response of antioxidants play an important role in the pathogenesis of CKD, both clinically and experimentally [ 14 , 32 , 36 , 54 ]. Due to its reactivity to lipids, ROS oxidize the lipids from cell membranes, causing lipid peroxidation, which eventually leads to the formation of reactive aldehydes, namely MDA, a bioactive marker that was measured in our study [ 36 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, they were sectioned into 4 µm pieces using a microtome from Leica Biosystems (Nussloch, Germany) and mounted onto slides. The slides were stained with hematoxylin and eosin (H&E) to assess acute tubular necrosis, Sirius red stain to evaluate interstitial fibrosis, and periodic acid Schiff (PAS) stain to assess the glomerular integrity [ 32 , 33 ]. The stained sections were blindly evaluated under a light microscope by a pathologist.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors speculate that the underlying mechanism of this renoprotective effect may be associated with glycemic control, lipid metabolism, and anti-oxidative and anti-inflammatory functions [ 69 ]. Al Za’abi et al found that metformin can be a useful drug in attenuating the progression of adenine-induced CKD in both diabetic and non-diabetic rats [ 70 ]. Increasing numbers of studies are investigating whether metformin exerts its hypoglycemic effect through the modulation of microbiome in the diabetic rat gut [ 71 ].…”
Section: Pharmacological Treatment Of T2dmmentioning
confidence: 99%